Food Policy Processes in the City of Rome: A Perspective on Policy Integration and Governance Innovation - Minotti, Bianca; Cimini, Angela; D'Amico, Gabriella; Marino, Davide; Mazzocchi, Giampiero; Tarra, Simona (Frontiers in Sustainable Food Systems, 2022)
In the food policy arena, the topic of governance and how to create a governance system that would deal with cross-cutting issues, including new ways of perceiving the public sphere, the policy-making and the involvement of the population, has become an important field of study. The research presented in this article focuses on the case study of Rome, comparing different paths that various groups of actors have taken towards the definition of urban food policy processes: the Agrifood Plan, Food Policy for Rome and Community Gardens Movement. The aim of the research is to understand the state of the art about different paths towards food strategies and policies that are currently active in the Roman territory while investigating the relationship between policy integration and governance innovation structures. Indeed, this paper dives into the governance structure of three food policy processes, the actors and sectors involved, the goals and instruments selected to achieve a more sustainable food system for the city. In this context, their characteristics are analyzed according to an innovative conceptual framework which, by crossing two recognized theoretical systems, on policy integration and governance innovation frameworks, allows to identify the capacity of policy integration and governance innovation. The analysis shows that every process performs a different form of governance, implemented according to the actor and backgrounds that compose the process itself. The study demonstrates that governance innovation and policy integration are strongly linked and that the conception and application of policy integration changes according to the governance vision that a process has.